2007
DOI: 10.1007/s11606-007-0191-7
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Frequency of Emergency Department Visits for Chronic Obstructive Pulmonary Disease Exacerbation

Abstract: BACKGROUND:Little is known about the factors associated with frequency of emergency department visits (FEDV) in chronic obstructive pulmonary disease (COPD) patients with recurrent exacerbations. OBJECTIVE:To characterize the use of emergency department (ED) services in patients with COPD exacerbation and identify factors associated with FEDV. DESIGN:A prospective, multicenter cohort study.PATIENTS: Three hundred eighty-eight patients were included. Fifty-two percent were women and the median age was 69 years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 31 publications
3
35
0
Order By: Relevance
“…In the literature, some cohorts have a very high prevalence of hypertension (63.4%), 19 whereas others, including ours (42%), are within the 40% to 60% range. [20][21][22] Our congestive heart failure estimate 15 ; similarly, we found cohort members with a "COPDother" comorbidity (490.x, bronchitis, not specifi ed as acute or chronic), at less risk of subsequent hospital admission. Interestingly, "substance-related disorders" comorbidity, although present in only a small percentage (1.5%, 512 of 33,799) of the cohort, had the largest association with increased subsequent hospital admission among the comorbidities we examined.…”
Section: Comorbiditiessupporting
confidence: 61%
See 2 more Smart Citations
“…In the literature, some cohorts have a very high prevalence of hypertension (63.4%), 19 whereas others, including ours (42%), are within the 40% to 60% range. [20][21][22] Our congestive heart failure estimate 15 ; similarly, we found cohort members with a "COPDother" comorbidity (490.x, bronchitis, not specifi ed as acute or chronic), at less risk of subsequent hospital admission. Interestingly, "substance-related disorders" comorbidity, although present in only a small percentage (1.5%, 512 of 33,799) of the cohort, had the largest association with increased subsequent hospital admission among the comorbidities we examined.…”
Section: Comorbiditiessupporting
confidence: 61%
“…However, these detailed codes (491, 492, 496) have been shown to have good sensitivity (85%) and modest specifi city (78.4%). 8,27 Second, we chose to of 21% was substantially higher than the 5% to 7% in Soriano et al 23 and Curkendall et al 22 but closer to the 15% found by Tsai et al 15 Some of these differences are likely due to the proportion of one sex vs another among the cohorts; other differences may be due to variations in ED coding practices.…”
Section: Comorbiditiesmentioning
confidence: 79%
See 1 more Smart Citation
“…These conditions are known as Ambulatory Care Sensitive Conditions (ACSCs) and include, as an example, diabetes, respiratory diseases, various cardiovascular diagnoses, and convulsive disorders 36 . The protective effect of GP accessibility and the pattern of GP contact against potentially preventable hospital admissions and adverse health events has been supported by several previous studies 35, [37][38][39][40][41] . As an example, high primary care physician density appears to protect against potentially preventable hospital admissions 35 , whereas lack of a 40 , and lack of access to primary care 41 appear to lead to increase in preventable hospitalisations.…”
Section: Discussionmentioning
confidence: 59%
“…We have shown that the frequency of ED visits for AECOPD is associated with not only disease factors, but also healthcare-related factors. 29 The consistently high ED visits for AECOPD might be related to the remaining challenges in our healthcare system, such as shortage of primary care and ⁄ or lack of universal insurance coverage. 30 The significant improvement in some ED treatments of AECOPD nicely parallels the advance in our understanding of AECOPD over the past decades.…”
Section: Discussionmentioning
confidence: 99%